Binding Energy‐dependent Growth Behaviors and Surface Characteristics of Sequentially Polymerized Zincone Films. (5th December 2019) - Lee, Hyemi; Choi, Ui‐Jin; Kim, Heewon; Lee, Jin Seok
Abstract : The influence of precursors on the growth of organic films has been studied intensively, but research on their binding energy‐dependent growth behaviors and surface properties has remained an undeveloped field. Herein, we conducted molecular layer deposition of zincone films on two metal oxide substrates, SiO2 and Al2 O3, and investigated the binding energy‐dependent growth behaviors and surface properties of the films experimentally. We also performed density functional theory calculations to determine the molecular geometries and surface binding energies of the films on each substrate. We established that the growth and surface characteristics of the films in the initial stages of deposition were strongly influenced by their surface binding energies, which depended on the substrate. Abstract : The influence of surface binding energy on the growth behaviors and surface properties of organic films deposited on metal oxide substrates were investigated.